(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine factors related to nutritional status using the GLIM tool in elderly patients with chronic obstructive pulmonary disease at University Medical Center Ho Chi Minh City. Subject and methods: A cross-sectional study was conducted among 251 older patients (≥ 60 years old) with chronic obstructive pulmonary disease who visited the University Medical Center Ho Chi Minh City from December 2023 to May 2024. The information collected included socio-demographic characteristics, pathological characteristics, nutritional status (as measured by GLIM), and body composition measurements. Results: Factors related to nutritional status as per GLIM include: age, bone mineral mass, basal metabolic energy/weight, and phase angle. Factors that increase the risk of malnutrition are older age and higher basal metabolic energy/weight, with ORs of 1.10 and 1.80, respectively. Increasing bone mineral mass and phase angle will reduce the risk of malnutrition with OR < 1. Conclusion: The rate of malnutrition remains high in elderly patients with chronic obstructive pulmonary disease, especially in those with advanced age and a decline in body composition.